ROLE OF COMPREHENSIVE TOTAL QUALITY MANAGEMENT IN ENHANCING THE IMPORTANCE OF THE INSURANCE COMPANY-AN APPLIED STUDY IN THE NATIONAL GENERAL INSURANCE COMPANY/IRAQ - Sami Abdullah Kadhim; Liqaa Miri Habeeb (Scholars Digest Publishing, 2024)
This study focuses on examining the impact of the dimensions of Total Quality Management (TQM)-(Customer Focus (CF), Customer Needs (CN), Acquiring Clients (AC)) on the dimensions of  Insurance Company (IC)-( Regulator Trust (RT), Information Trust (IT)) In organizations. This study relied on studying the dimensions of variables to increase the productive efficiency of organizations. A sample of employees in an applied study in the insurance company/Iraq. The researcher in this study adopted a questionnaire form to collect the required data by distributing it to the employees. The number was (136), and (8) forms were incorrect. Valid questionnaires were obtained (128). This study relied on the statistical analysis of the results on the SPSS & Smart-PLS 4 program. The researcher reached a number of results and conclusions that were necessary in his work and were highly efficient. This study focused on the importance of the dimensions of total quality management in achieving the required goals. In this study, the researcher emphasized a number of recommendations that were reached and documented the important relationship between the dimensions of comprehensive quality management and the dimensions of the insurance company.
Keywords: dimensions of comprehensive quality management, dimensions of the insurance company, Iraqi insurance company, planning, organization.